Intercropping of fenugreek as living mulch at different densities for weed suppression in coriander. (March 2015) - Pouryousef, Majid; Yousefi, Ali Reza; Oveisi, Mostafa; Asadi, Fatemeh
Abstract: Living mulch planted between rows might limit weed growth. The objective of this study was to determine the weed-suppressing effect of fenugreek intercropped with coriander, with the aim to select a suitable density of fenugreek for intercropping in coriander production. Five fenugreek densities and three weed control levels were evaluated in a factorial arrangement of treatments. Results indicated that increasing density of fenugreek living mulch suppressed weed growth and increased seed yield compared to weed infested conditions. Maximum weed biomass was recorded in sole coriander with no control (329 and 274 g m −2 in 2012 and 2013, respectively), while minimum weed biomass was recorded in plots which fenugreek intercropped at the density of 50 plants m −2 and one hand weeding was applied. Increasing fenugreek density decreased the LAI of coriander with similar gentle slopes for both years. The seed yields obtained from weed free, one hand weeding, and no control plots were 1618, 973, and 457 kg ha −1, respectively. With increase in weed control level fenugreek density caused a decrease with greater impact on the coriander seed yield. Essential oil content from dried fruit ranged from 0.52 to 1.14% and 0.52 to 1.10% in 2012 and 2013, respectively. Our findings confirm that fenugreek can be used as living mulch in organic coriander production to reduce the biomass of weeds. However, the use of fenugreek did not provide reliable weed control throughout the season and so must be combined with additional weed management options to achieve acceptable control. Highlights: Weed-suppressing effect of fenugreek intercropped in coriander was studied. Fenugreek living mulch at all the density tested suppressed weed growth. Living mulch increased seed yield over the weedy sole coriander.